2020
DOI: 10.3389/fcell.2020.00383
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Circuit Orchestrated by Novel-miR-3880 Modulates Mammary Gland Development

Abstract: Milk casein and triglyceride content are important production traits in goats. Studies on mechanisms in milk casein secretion and mammary gland development is essential for milk goat breeding. miRNAs play an important role in goat lactation. While novel-miR-3880 is highly expressed at goat peak lactation stage, its molecular mechanism has not been studied. The purpose of the present study was to explore the relationship between novel-miR-3880 and lactation, as well as to construct a network among novel-miR-388… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The final protein product shows different or antagonistic functional and structural characteristics compared with unspliced RNA or lead to different phenotypes due to different expression levels in the same cell ( Zhang et al, 2016 ). For example, Zang et al (2020) found that circRNAs can participate in the regulation of splicing and transcription. Chao et al (1998) found that the mouse Fmn gene can produce circRNA through “backsplicing”.…”
Section: Circular Rnasmentioning
confidence: 99%
“…The final protein product shows different or antagonistic functional and structural characteristics compared with unspliced RNA or lead to different phenotypes due to different expression levels in the same cell ( Zhang et al, 2016 ). For example, Zang et al (2020) found that circRNAs can participate in the regulation of splicing and transcription. Chao et al (1998) found that the mouse Fmn gene can produce circRNA through “backsplicing”.…”
Section: Circular Rnasmentioning
confidence: 99%
“…10 In addition, novel-mir-3880 played a regulatory role in breast development and milk synthesis, which showed high expression in the mammary gland of dairy goats at the peak of lactation. 11 What is more, Circ-8073, as a ceRNA, cooperated with mir-449/34 family through CEP55-FOXM1-VEGFA to regulate the establishment of milk goat receptive endometrium. 12 Based on their special regulatory function in cells, in dairy goat breeding, some miRNAs play important roles in the establishment of endometrial receptivity.…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is the best source of nutrition for infants [ 2 ]; therefore, it is important to prevent mammary gland involution. MicroRNAs (miRNAs) are a class of endogenous non-coding RNAs with a length of 18–23 nucleotides that play essential roles in lactation [ 3 , 4 ]. Chi-miR-8516 is one of the miRNAs that has been reported to show higher expression in the common milk stage, compared to colostrum stage [ 5 ].…”
Section: Introductionmentioning
confidence: 99%